دراسة محددات الشراء لدى مستهلكي لحم الدجاج في محافظة اللاذقية - فاروسي, عمر; عليو, محمود; خضور, ايهاب (Latakia University Journal -Biological Sciences Series, 2017)
هدف البحث إلى دراسة محددات الشراء لدى مستهلكي لحم الدجاج في محافظة اللاذقية، ومعرفة مدى تأثر المستهلك بها عند اتخاذ قرار الشراء، بلغت العينة المبحوثة (500) مستهلك، وتم توزيع استمارة استبيان خصصت لهذا الغرض.استخدم المنهج الإحصائي والتحليلي من أجل دراسة وتحليل البيانات، حيث استخدم تصميم العشوائية الكاملة، واختبار F وفق البرنامج الإحصائي SPSS. وتوصل البحث إلى مجموعة من النتائج أهمها:• تأثر قرار الشراء بمجموعة من العوامل وهي: مستوى دخل المستهلك – مواصفات المنتج – سعر لحم الدجاج – أسعار اللحوم الأخرى – آراء الأصدقاء.• انخفاض تأثير عمر المستهلك، وآراء البائع، والإعلان على عملية اتخاذ قرار الشراء.The research aims to study the determinants of purchase to the consumers of chicken meat in the province of Latakia, and see how it affected the consumer when making a purchase decision, respondents were surveyed (500) the consumer, was the distribution of a questionnaire allocated for this purpose.Use the statistical and analytical method for the study and analysis of the data, which used randomized complete block design, and testing of F in accordance with the SPSS statistical program, the research found a range of results, including:• purchasing decision influenced by a variety of factors: the level of consumer income - Product Specifications - the price of chicken meat - other meat prices - the views of friends. • Low impact of consumer life and the views of the seller and the Declaration on the purchase decision process.